2013
DOI: 10.1016/j.yexmp.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 regulates a novel form of incomplete neoplastic transformation of Theileria parva infected lymphocytes

Abstract: Our efforts are concerned with identifying features of incomplete malignant transformation caused by non viral pathogens. Theileria parva (T. parva) is a tick-transmitted protozoan parasite that can cause a fatal lymphoproliferative disease in cattle. The T. parva-infected lymphocytes display a transformed phenotype and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 53 publications
(48 reference statements)
1
37
0
Order By: Relevance
“…We did not find evidence for changes in the expression of these two miRNAs upon Theileria infection. It is also possible that miRNA targeting of ubiquitination machinery may contribute to other aspects of Theileria -induced host signaling, such as effects on p53 and NFκB pathways [16], [45].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find evidence for changes in the expression of these two miRNAs upon Theileria infection. It is also possible that miRNA targeting of ubiquitination machinery may contribute to other aspects of Theileria -induced host signaling, such as effects on p53 and NFκB pathways [16], [45].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that apicomplexan parasites directly target the p53 pathway; for example, Theileria annulata infection was linked to cytoplasmic sequestration of p53 and physical association with parasite membranes (Haller et al, 2010). T. parva -infected lymphocytes have increased levels of MDM2, with alternatively spliced isoforms and impaired DNA damage responses (Hayashida et al, 2013). Parasite-encoded proteins responsible for manipulating host pathways have remained relatively elusive.…”
Section: Pathogen Oncoproteins and Genotoxins And Their Intersection mentioning
confidence: 99%
“…NF-kB regulates a multitude of biological processes and is ubiquitously activated in hematological malignancies [14,15]. Pattern-recognition receptors can also activate NF-kB to induce in vivo antimicrobial programs that are crucial for innate and adaptive immunity [16], and many pathogens have the ability to suppress NF-kB signaling [17,18]. The IkB kinase (IKK) complex activates NF-kB, and Theileria schizonts have been shown to constitutively activate the IKK complex on their cell surface, possibly by trans-autophosphorylation [19].…”
Section: Mechanisms Of Theileria-induced Proliferative Signalingmentioning
confidence: 99%
“…Mechanisms of telomerase-dependent immortalization have been the target of intense study in the cancer research community. Telomerase inhibitors effectively restrict T. parva-induced transformation [18]. Recent work has shown that human telomerase, hTERT, can bind to the p65 NF-kB subunit and direct it to a subset of NF-kB The definitive host is a tick (Rhipicephalus for T. parva and Hyalomma for T. annulata), which ingests piroplasms from the blood of an infected bovine host.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation